Evolution of Baitul Maal Wat-Tamwil: From Early Islamic Social Finance to Digital Islamic Microfinance in Indonesia - A. Muh Nursyahid; Dedy Rachmad (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2026)
Baitul Maal wat-Tamwil (BMT) is a community-based Islamic microfinance institution that integrates the redistributive function of baitul maal with the productive financing function of baitul tamwil. However, regulatory formalization, financial sustainability pressures, and digital transformation may alter the balance between these social and commercial functions. This study analyzes the historical evolution and institutional transformation of BMT in Indonesia and evaluates its implications from the perspective of Islamic economic law. It employs qualitative library research using historical, conceptual, and juridical approaches. Primary materials comprise legislation, regulatory policies, fatwas, and Islamic legal sources, while secondary materials include books, journal articles, and research reports. The materials were examined through qualitative content analysis and classified into historical, institutional, regulatory, digital, and Sharia-related themes. The analysis indicates that BMT has evolved from the normative foundations of early Islamic social finance into a hybrid, formally regulated, and increasingly digital microfinance institution. Digitalization can improve efficiency, transparency, service accessibility, and social-fund management, but it may also reinforce the dominance of the tamwil function, create digital exclusion, and increase cybersecurity and personal-data risks. From the perspective of Islamic economic law, BMT transformation remains legitimate when it ensures substantive Sharia compliance, contractual justice, transparent fund separation, consumer and data protection, effective Sharia supervision, and the achievement of maqāṣid al-sharī‘ah. BMT modernization should therefore integrate financial, social, Sharia, and digital sustainability while preserving its commitment to community empowerment.